Comprehensive Proteomic Analysis of Lysine Acetylation in the Foodborne Pathogen Trichinella spiralis - Yang, Yong; Tong, Mingwei; Bai, Xue; Liu, Xiaolei; Cai, Xuepeng; Luo, Xuenong; Zhang, Peihao; Cai, Wei; Vallée, Isabelle; Zhou, Yonghua; Liu, Mingyuan (Frontiers in Microbiology, 2018)
Lysine acetylation is a dynamic and highly conserved post-translational modiﬁcation that plays a critical role in regulating diverse cellular processes. Trichinella spiralis is a foodborne parasite with a considerable socio-economic impact. However, to date, little is known regarding the role of lysine acetylation in this parasitic nematode. In this study, we utilized a proteomic approach involving anti-acetyl lysine-based enrichment and highly sensitive mass spectrometry to identify the global acetylated proteome and investigate lysine acetylation in T. spiralis. In total, 3872 lysine modiﬁcation sites were identified in 1592 proteins that are involved in a wide variety of biological processes. Consistent with the results of previous studies, a large number of the acetylated proteins appear to be involved in metabolic and biosynthetic processes. Interestingly, according to the functional enrichment analysis, 29 acetylated proteins were associated with phagocytosis, suggesting an important role of lysine acetylation in this process. Among the identified proteins, 15 putative acetylation motifs were detected. The presence of serine downstream of the lysine acetylation site was commonly observed in the regions surrounding the sites. Moreover, protein interaction network analysis revealed that various interactions are regulated by protein acetylation. These data represent the first report of the acetylome of T. spiralis and provide an important resource for further explorations of the role of lysine acetylation in this foodborne pathogen.